Leptin Inhibits the Proliferation of Vascular Smooth Muscle Cells Induced by Angiotensin II through Nitric Oxide-Dependent Mechanisms - Amaia Rodríguez; Javier Gómez-Ambrosi; Victoria Catalán; Ana Fortuño; Gema Frühbeck (Mediators of Inflammation)
Objective. This study was designed to investigate whether leptin modifies angiotensin (Ang) II-induced proliferation of aortic vascular smooth muscle cells (VSMCs) from 10-week-old male Wistar and spontaneously hypertensive rats (SHR), and the possible role of nitric oxide (NO). Methods. NO and NO synthase (NOS) activity were assessed by the Griess and 3H-arginine/citrulline conversion assays, respectively. Inducible NOS (iNOS) and NADPH oxidase subutnit Nox2 expression was determined by Western-blot. The proliferative responses to Ang II were evaluated through enzymatic methods. Results. Leptin inhibited the Ang II-induced proliferative response of VSMCs from control rats. This inhibitory effect of leptin was abolished by NOS inhibitor, NMMA, and iNOS selective inhibitor, L-NIL, and was not observed in leptin receptor-deficient fa/fa rats. SHR showed increased serum leptin concentrations and lipid peroxidation. Despite a similar leptin-induced iNOS up-regulation, VSMCs from SHR showed an impaired NOS activity and NO production induced by leptin, and an increased basal Nox2 expression. The inhibitory effect of leptin on Ang II-induced VSMC proliferation was attenuated. Conclusion. Leptin blocks the proliferative response to Ang II through NO-dependent mechanisms. The attenuation of this inhibitory effect of leptin in spontaneous hypertension appears to be due to a reduced NO bioavailability in VSMCs.